Calcaneum tuberculosis-an uncommon phenomenon: narrative review - Kumar, Sumit; Kumar, Rajendra; Jayant, Neeraj; Gautam, Chandrakant; Aggarwal, Vipul (International Journal of Research in Orthopaedics, 2025)
The Mycobacterium tuberculosis is the cause of tuberculosis (TB), a dangerous and highly contagious infection that is a major source of morbidity and mortality. One to three percent of cases have osteoarticular TB, and 10% of these cases involve foot and ankle involvement. The bone in the foot most frequently attacked by TB is the calcaneus. There are currently relatively few case series studies and case Report available that describe this uncommon phenomenon. The aim of this narrative review is to find information on the calcaneum tuberculosis-An uncommon phenomenon. We evaluated the medical records of some patients with 4 to 68 years, who had isolated calcaneal tuberculous osteomyelitis. As part of the systematic search, the phrase "calcaneal tuberculosis-an uncommon phenomenon" was created in relation to integrative, along with its synonyms, and the search database was used. The Google search engine was used to manually search PubMed and Google Scholar. The database did not include any further articles. According to the study’s conclusions, Mycobacterium tuberculosis is the main cause of TB, a dangerous and communicable infectious illness. Calcaneal tuberculosis is uncommon. A high degree of clinical suspicion, in addition to positive imaging data, GeneXpert findings, and Gram stains, can aid in the diagnosis of TB calcaneus because it is an uncommon illness. To stop the illness from spreading to other bones and joints, early identification is crucial. Patient was treated with antitubercular medication and had a successful operation to correct the abnormalities.